Development of process framework for ontology construction through ontology mapping / Syerina Azlin Md Nasir (Institute of Graduate Studies, UiTM, 2016)
Digitization of cultural heritage collections, both within and outside museums has led to the establishment of a new field of theory and practice of the digital curation of cultural information. Cultural heritage ontology construction a practice in museum documentation, faces the challenge of dealing with the abundance of information while struggling to maintain the authenticity and preservation of the cultural knowledge. Similar to other knowledge domains, the existence of various ontology of cultural heritage knowledge and their differences has caused predicament in accessing or retrieving information. To overcome this predicament, the standard ontology, in this case the CIDOC CRM is used to consolidate between two or more local ontology through the consolidation with a standard (global) ontology through a process known as ontology mapping. The effort needed to map two ontologies with some content similarity but different structures while minimizing knowledge loss is challenging. Knowledge loss is a situation where the concepts of local ontology are excluded from the result of mapping to the global ontology. Automated mapping through the use various existing algorithms offers an efficient solution but suffers in knowledge loss. A compromised method is needed to balance between the construction efficiency and the knowledge loss. This research seeks to establish a framework for constructing cultural heritage ontology through semi-automated ontology mapping. Using the traditional Malays textile (TMT) as the domain knowledge for this work and scoping on the Malaysian batik, this research is carried out in three phases…